Features of the formation and management of the unified network of the state and local budgets of the Volyn oblast - Onysiuk, Vitalii (Луцьк: Вежа-Друк, 2024)
The formation of the network by managers of state and local budget funds is regulated by the Procedure for treasury service of local budgets, approved by order of the Ministry of Finance of Ukraine dated 23.08.2012 No. 938 (hereinafter – Order No. 938) and the Procedure for treasury service of the state budget by expenses, approved by order of the Ministry of Finance of Ukraine dated 24.12. 2012 No. 1407 (hereinafter – Order No. 1407). In accordance with the requirements of Section 4 of Order No. 938 and Section II of Order No. 1407, the network consists by the main managers of budget funds and managers of lower-level funds that have their own network.
Keywords: state budget; local budgets; budgetary institution; 336.14(477.82)